Dampak Instabilitas Inflasi, BI Rate dan Kurs terhadap Suku Bunga PUAB 2009-2019 - Izza Aisha Rahmadiah; Desmintari Desmintari; Indri Arrafi Juliannisa (Jurnal Indonesia Sosial Teknologi, 2022)
The Liberalization of the PUAB Interest Rate is a reference used by banks and applied by the central bank for transactions in the Indonesian money market. The interbank Rate itself can be influenced by several variables, including inflation, the BI Rate and the exchange Rate. The purpose of this study is to determine the effect of inflation, BI Rate and exchange rate on changes in interbank rates. The data used in this study is quarterly data from 2009-2019. The method used is the OLS method with multiple linear analysis models. The results of multiple regression analysis show that (1) there is a significant effect between inflation on the PUAB Interest Rate (2) there is no significant effect between the BI Rate on the PUAB Interest Rate (3) there is a significant effect between the exchange rate on the PUAB Interest Rate.